THORACIC RADIOGRAPHIC CHARACTERISTICS OF CANINE INFLUENZA VIRUS IN SIX DOGS. Issue 5 (7th July 2016) - Secrest, Scott A.; Sharma, Ajay
Abstract : Canine influenza virus is an emerging, highly contagious, respiratory pathogen that has not previously been radiographically described. In this retrospective case series study, we describe the thoracic radiographic appearance of confirmed canine influenza virus in six dogs. Radiographic findings varied, but included abnormal unstructured interstitial (one) and unstructured interstitial and alveolar (five) pulmonary patterns, which were distributed cranioventral (four), diffuse (one), and caudodorsal (one). The right middle (five), left cranial (five), and right cranial (four) lung lobes were most commonly affected. Additionally, mild pleural effusion was present in one dog. Intrathoracic lymphadenopathy and cranial mediastinal widening/fluid accumulation were not detected in any dog. Canine influenza virus should be considered as a differential diagnosis for canine patients with respiratory signs and a cranioventral unstructured interstitial to alveolar pulmonary pattern.